1999
DOI: 10.1182/blood.v94.2.781
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Iron Chelators of the Pyridoxal Isonicotinoyl Hydrazone Class as Effective Antiproliferative Agents III: The Effect of the Ligands on Molecular Targets Involved in Proliferation

Abstract: We have identified specific iron (Fe) chelators of the pyridoxal isonicotinoyl hydrazone (PIH) class that are far more effective ligands than desferrioxamine (DFO; Richardson et al, Blood 86:4295, 1995; Richardson and Milnes, Blood 89:3025, 1997). In the present study, we have compared the effect of DFO and one of the most active chelators (2-hydroxy-1-naphthylaldehyde isonicotinoyl hydrazone; 311) on molecular targets involved in proliferation. This was performed to further understand the mechanisms involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
72
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(82 citation statements)
references
References 41 publications
10
72
0
Order By: Relevance
“…The antiproliferative effect of iron chelating agents has been well recognized. ( 4,7,16–18 ) However, in the past, the exact mechanism of the antineoplastic effects of iron chelator were not clearly determined. Among iron chelators, deferasirox has been shown to have higher antiproliferative effects by apoptosis in cultured human hepatocytes and hepatocellular carcinoma cell lines than O‐trensox, ( 19,20 ) and deferasirox is now available as an oral iron chelator.…”
Section: Discussionmentioning
confidence: 99%
“…The antiproliferative effect of iron chelating agents has been well recognized. ( 4,7,16–18 ) However, in the past, the exact mechanism of the antineoplastic effects of iron chelator were not clearly determined. Among iron chelators, deferasirox has been shown to have higher antiproliferative effects by apoptosis in cultured human hepatocytes and hepatocellular carcinoma cell lines than O‐trensox, ( 19,20 ) and deferasirox is now available as an oral iron chelator.…”
Section: Discussionmentioning
confidence: 99%
“…We were specifically interested in the recent application of coordination complexes of Group 13 metal ions with fluoride. McBride et al and others [41][42][43][44][45][46][47][48] have reported the formation of inorganic aluminium complexes with the radioisotope 18 F which show excellent stability, and have highlighted that these provide simple moieties which can be incorporated into a wide range of biomolecules with potential as positron emitting tomography (PET) imaging agents. We prepared new semicarbazones and thiosemicarbazones and their copper complexes, studied their structural characteristics and evaluated their biological profiles.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In the recent years attention has focussed on the biological applications of these compounds. In this regard, it has been found that some thiosemicarbazones have potent anticancer activity [4][5][6][7][8][9][10][11][12][13][14] The use of iron chelators containing thiosemicarbazones has also been extensively studied [15][16][17][18][19][20][21][22][23][24][25][26] as has the anticancer activity of novel thiosemicarbazones generated through the combination of retro fragments. Some thiosemicarbazones have been found to have antibacterial and antifungal activity [27][28][29] and the pharmacological profile of thiosemicarbazones attached to a heterocyclic core has been reported by Singhal et al [30] The biological profile exhibited by these thiosemicarbazone and semicarbazone derivatives has led to work in which these compounds have been complexed with positron emitting isotopes (e.g.…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%
“…14 Iron chelators enhance the expression of several genes, involved in the downregulation of cell cycle progression, such as WAF1 and GADD45, in a p53-independent mechanism. 15 In addition, cdc2 (p34) protein levels, which regulate the checkpoint of the G2/M phase transition, are decreased following incubation with iron chelators. 16 A group from Sydney, Australia, specialized on iron metabolism has reported that iron depletion with deferroxamine (DFO) is associated with substantial decrease of cyclin D1 levels, through post-transcriptional modification of the protein, in a ubiquitin-independent manner, in contrast to what happens under normal conditions, in which cyclin D1 is cleared through proteasomal degradation.…”
Section: The Role Of Iron In Normal Cell Growthmentioning
confidence: 99%